The Effectiveness of Using Learning Device Information Systems in Preparing Learning Plans - Rohita; Nadhifah Rahmadini Hidayat (Program Studi Magister Pendidikan Anak Usia Dini, 2023)
The importance of the ability to develop lesson plans requires educators to be able to understand and master learning content as well as understand various ways to complete it. The learning device information system (SIPP) as one of the results of technology is here to help educators complete this task. The purpose of this study was to demonstrate the effectiveness and efficiency of SIPP in developing learning plans in early childhood education. The research was conducted using a quantitative approach, with descriptive statistical analysis presented in the form of a frequency distribution table. The questionnaire was distributed using a Likert scale, which contains items regarding goal achievement, quality, output, and user response as indicators of effectiveness and contains items regarding the use of time, cost, effort, and use of paper materials as indicators of efficiency. The results showed that the four indicators of effectiveness were met with an average score of 385.8. Efficiency which includes four indicators achieves an average score of 19.3. The availability of components in templates that are adjusted to the applicable provisions and can be used automatically allows users to complete their tasks in a relatively faster time. The availability of components in templates that are adjusted to the applicable provisions and can be used automatically allows users to complete their tasks in a relatively faster time. The conclusion is that SIPP is very effective and efficient for preparing lesson plans so that it can facilitate and save the teacher's time in completing the task. Keywords: learning device information; early childhood education, lesson plan References: Abdurohman, M., Kuspriyanto, Sutikno, S., & Sasongko, A. (2010). Perancangan Aturan Transformasi UML-Systemic dalam Perancangan Embedded System. Jurnal Ilmu Komputer Dan Informasi, 3(2), 91–97. https://doi.org/hhttps://doi.org/10.21609/jiki.v3i2.146 Adnan, K., & Bataineh, A. (2014). Impacts of Employee Training on the Performance of Commercial Banks in Jordan. European Journal of Business and Management Www.Iiste.Org ISSN, 6(27), 192–197. Afeanpah, F. (2017). Komentar Tentang Paperless Office. Paperless Office. Afendi, M. (2019). Penggunaan Media Lingkungan Berbasis Eksperimen sebagai Alat Bantu Terciptanya Tujuan Pendidikan. Seminar Nasional Pendidikan FKIP, 2(1), 596–608. Ahmad, & Pambudi, B. S. (2014). Pengaruh Persepsi Manfaat, Persepsi Kemudahan, Keamanan dan Ketersediaan Fitur Terhadap Minat Ulang Nasabah Bank dalam Menggunakan Internet Banking (Studi pada Program Layanan Internet Banking BRI). Jurnal Studi Manajemen, 8(1), 2–11. https://doi.org/https://doi.org/10.21107/kompetensi.v8i1.589 Apriyansyah, Maullidina, I., & Purnomo, E. P. (2018). Efektivitas sistem informasi desa (SID) dalam pelayanan publik di Desa Dlingo, Kecamatan Dlingo, Kabupaten Bantul. Jurnal Analisis Kebijakan Dan Pelayanan Publik, 4(1), 10–24. https://doi.org/http://dx.doi.org/10.31947/jakpp.v4i1.5901 Arza, W. (2019). New Aplikasi Raport K13 Paud/TK/RA (ERA Erlangga). YouTube. Astriani, S. A. (2018). Prinsip & Kriteria Pemilihan Media Pembelajaran. Universitas Nurul Jadid. Astuty, E. Y., & Chandra, A. N. (2016). Rancang Bangun Aplikasi Sistem Pendukung Keputusan untuk Menentukan Tingkat Keahlian User pada PT. Willong Atlantik Jakarta. Jurnal Sains & Teknologi, VI(2), 103–118. Baker El-Ebiary, Y. A., Mjlae, S. A., Abu-Ulbeh, W., Hassan, A. H., Bamansoor, S., & Saany, S. I. A. (2020). The Effectiveness of Management Information System in Decision-Making. Journal of Mechanics of Continua and Mathematical Sciences, 15(7), 316–327. https://doi.org/10.26782/jmcms.2020.07.00026 Beny, B., Yani, H., & Ningrum, G. M. (2019). Evaluasi Usability Situs Web Kemenkumham Kantor Wilayah Jambi dengan Metode Usability Test dan System Usability Scale. RESEARCH : Computer, Information System & Technology Management, 2(1), 30–34. https://doi.org/10.25273/research.v2i1.4282 Burhan, M. N. I., & Herman. (2019). Perilaku Prokrastinasi Akademik Mahasiswa (Studi Pada Mahasiswa Prodi Pendidikan Ilmu Pengetahuan Sosial Fakultas Ilmu Sosial Universitas Negeri Makassar). In Social landscape journal pendidikan ilmu pengetahuan sosial. Universitas Negeri Makassar. Creswell, J. W., & Clark, V. L. P. (2017). Designing and Conducting Mixed Methods Research-SAGE Publications. Creswell, W. J., & Creswell, J. D. (2018). Research Design: Qualitative, Quantitative adn Mixed Methods Approaches. In Journal of Chemical Information and Modeling (Vol. 53, Issue 9). file:///C:/Users/Harrison/Downloads/John W. Creswell & J. David Creswell - Research Design_ Qualitative, Quantitative, and Mixed Methods Approaches (2018).pdf%0Afile:///C:/Users/Harrison/AppData/Local/Mendeley Ltd./Mendeley Desktop/Downloaded/Creswell, Cr Dindayani, N., Menne, F., & Mane, A. (2019). Analisis sistem informasi akuntansi penjualan tunai dalam menunjang efektivitas dan efisiensi sistem pengendalian intern pada PT Optik Tunggal Sempurna Cabang Mall Ratu Indah. Economics Bosowa Journal, 5(002), 108–122. Fatmawati, N., Sofia, A., Drupadi, R., Nawangsasi, D., Irzalinda, V., & Sugiana. (2019). Pelatihan penyusunan perangkat pembelajaran kurikulum 2013 bagi guru pendidikan anak usia dini (PAUD). Seminar Nasional Pendidikan Forkom PG PAUD 2019, 8–14. Febriana, R. (2019). Kompetensi guru (B. S. Fatmawati (ed.); Pertama). Bumi Aksara. Fitria, N., & Rohita. (2019). Content Analysis of Kindergarten Daily Learning Implementation Plans ( RPPH ) in Central Jakarta Region. International Symposium on Social Sciences, Education, and Humanities, 306(Isseh 2018), 152–158. Fitria, N., Rohita, & Zahrawanny, V. P. (2019). Kindergarten teacher’s ability in developing kindergarten learning planning in Kebayoran Baru District. Proceedings of ISER-ACN, December, 7–9. Hendarwati, E., Setiawan, A., & Rahayu, A. P. (2017). Pelatihan pembelajaran inovatif, penyusunan perangkat pembelajaran dan pembukuan pada Bunda PAUD. AKSIOLOGIYA : Jurnal Pengabdian Kepada Masyarakat, 1(2), 81–91. https://doi.org/10.30651/aks.v1i2.748 Himawan. (2019). Review dan Analisa Faktor-Faktor yang Mempengaruhi Kecepatan Akses Halaman Website. Ultimatics : Jurnal Teknik Informatika, 11(1), 38–45. https://doi.org/10.31937/ti.v11i1.1060 Humaedi, M. A. (2015). Etnografi bencana: Menakar peran para pemimpin lokal dalam pengurangan resiko bencana. LKiS Yogyakarta. Irviani, R., & Setiawan, P. (2017). Aplikasi Berbagi Pesan Berbasis Web Sebagai Media Komunikasi Di Stmik Pringsewu. Semnasteknomedia Online, 5(1), 4-7–13. https://ojs.amikom.ac.id/index.php/semnasteknomedia/article/view/1819/1541 Kaleb, B. J., Lengkong, V. P. ., & Taroreh, R. N. (2019). Penerapan Sistem Informasi Manajemen dan Pengawasannya di Kantor Pelayanan Pajak KPP Pratama Manado. Jurnal EMBA, 7(1), 781–790. Kemdikbud. (2015a). Peraturan Menteri Pendidikan dan Kebudayaan Republik Indonesia Nomor 137 Tahun 2013 Tentang Standar Nasional Pendidikan Anak Usia Dini. Kementrian Pendidikan dan Kebudayaan. Kemdikbud. (2015b). Peraturan Menteri Pendidikan dan Kebudayaan Republik Indonesia Nomor 146 Tahun 2014 Kurikulum 2013 Pendidikan Anak Usia Dini. Kementrian Pendidikan dan Kebudayaan. Khan, R. A. G., Khan, F. A., & Khan, M. A. (2011). The Impact of Training and Development on Organizational Performance. Global Journal of Management and Business Research, 11(7), 113–123. https://doi.org/10.24191/ji.v17i2.18177 Koloay, L. P., Morasa, J., & Elim, I. (2014). Peranan Sistem Informasi Akuntansi dalam Efektifitas Pelaporan Informasi Akuntansi Pertanggungjawaban Pada PT. POS Indonesia (Persero) Manado. 2(2), 1528–1538. Machmuddah, Z., & Suhartono, E. (2019). Peranan Aplikasi Sistem BOP PAUD yang Akuntabel untuk Guru PAUD Kota Semarang The Role of BOP PAUD System Aplication Accountable for PAUD Teachers in Semarang City. Abdimasku: Jurnal Pengabdian Masyarakat, 2(2), 114–120. https://doi.org/10.33633/ja.v2i2.45 Marading, N. (2019). Peningkatan kompetensi guru binaan dalam menyusun RPPH melalui workshop di Gugus PAUD Rantepao Kabupaten Toraja Utara. Indonesian Journal of Educational Studies (Ijes), 22(1), 8–15. https://doi.org/https://doi.org/10.26858/ijes.v22i1.9342 Masnipal. (2018). Menjadi Guru PAUD Profesional. PT Remaja Rosdakarya. Meliana, Julianto, V., & Hafidz, K. A. (2020). Sistem Informasi Manajemen Taman Kanak-Kanak (Studi Kasus: Taman Kanak-Kanak (TK) Mekar Sari Desa Ambawang). Aisyah Journal of Informatics and Electrical Engineering, 2(2), 145–151. https://doi.org/10.30604/jti.v2i2.39 Membara, E. P., Liza, Y., & Indra, K. (2014). Sistem informasi akademik SMP Negeri 2 Talang Empat berbasis web. Jurnal Infotama, 10(1), 72–80. Mudjiyanto, B. (2018). Tipe Penelitian Eksploratif Komunikasi. Jurnal Studi Komunikasi Dan Media, 22(1), 65–74. https://doi.org/10.31445/jskm.2018.220105 Mulyono, T. (2018). Sistem informasi E-Office pendukung program paperless korespondensi perkantoran (studi kasus : bagian administrasi akademik akademi komunitas semen Indonesia Gresik ). Jurnal Tecnoscienza, 2(2), 107–122. Munawaroh, S., Syukri, M., & Marmawi. (2019). Kompetensi guru dalam menyusun perangkat pembelajaran di PAUD Cahaya Desa Kapur Kecamatan Sungai Raya. Jurnal Pendidikan Dan Pembelajaran Khatulistiwa, 8(7), 1–8. Ndihokubwayo, K., Ndayambaje, I., & Uwamahoro, J. (2020). Analysis of Lesson Plans from Rwandan Physics Teachers. International Journal of Learning, Teaching and Educational Research, 19(12), 1–29. https://doi.org/https://doi.org/10.26803/ijlter.19.12.1 Neuman, W. L. (2018). Metode Penelitian Sosial: Pendekatan Kualitatif dan Kuantitatif (7th ed.). Indeks. Niati, A., Soelistiyono, A., & Ariefiantoro, T. (2019). Pengembangan Kemampuan Sumber Daya Manusia melalui Pelatihan Komputer Microsoft Office Excel untuk Meningkatkan Kinerja Perangkat Desa Mranggen. E-Dimas: Jurnal Pengabdian Kepada Masyarakat, 10(1), 105. https://doi.org/10.26877/e-dimas.v10i1.3557 Ningrum, O. S., & Puspasari, D. (2015). Penggunaan Aplikasi Google Drive Sebagai Penunjang Paperless Office. Jurnal Pendidikan Administrasi Perkantoran (JPAP), 3(3), 1–15. Nugroho, Y. S. (2015). Pengembangan Manajemen Data Elektronik PAUD di PAC Aisyiyah Kecamatan Tingkir, Salatiga. Warta LPM, 18(2), 110–117. https://doi.org/10.23917/warta.v18i2.1950 Oyitso, M., & Olomukoro. (2012). Training and Retraining Nigeria Workers To Enhance Task Performance. Interdisciplinary Journal of Contemporary Research in Business, 4(1), 69–78. https://journal-archieves18.webs.com/69-78.pdf Pamungkas, J., Hayati, N., & Maryatun, I. B. (2016). Pengembangan Perencanaan Pembelajaran Paud Berbasis Budaya. Jurnal Pendidikan Anak, 5(2), 831–839. https://doi.org/10.21831/jpa.v5i2.12389 Parsaorantua, P. H., Pasoreh, Y., & Rondonuwu, S. A. (2017). Implementasi Teknologi Informasi dan Komunikasi (Studi tentang Web E-Government di Kominfo Kota Manado). Acta Diurna Komunikasi, VI(3), 1–14. Prananda, A. A., & Datu, C. (2016). Peranan Sistem Informasi Akuntasi Manajemen dalam Pengambilan Keputusan Investasi Asset Tetap pada PT. ETMIECO Sarana Laut Bitung. Jurnal EMBA, 4(1), 1531–1541. https://doi.org/10.35794/emba.v4i1.12375 Purwanto, R. (2017). Penerapan sistem informasi akademik (SIA) sebagai upaya peningkatan efektifitas dan efisiensi pengelolaan akademik sekolah. Jurnal Teknologi Terapan, 3(2), 24–31. Rafael, A. M. D., Feka, V. P., Nama, D. Y., Nitte, Y. M., & Benu, A. Y. (2021). Pelatihan Media Pembelajaran Powtoon Untuk Pembelajaran Bahasa bagi Guru PAUD Pelangi dan Guru TK Mentari, Balai Pendidikan PAUD Kota Kupang. Pemimpin: Pengabdian Masyarakat Ilmu Pendidikan, 1(1), 37–43. Rahman, F., Nabi Bux, J., Akhter, Y., Saeed Ul Hasan, C., & Ajmal, M. (2011). Relationship Between Training Of Teachers And Effectiveness Teaching. International Journal of Business and Social Science, 2(4), 150–160. http://search.proquest.com/docview/904524261?accountid=12253%5Cnhttp://openurl.man.ac.uk/sfxlcl3?url_ver=Z39.88-2004&rft_val_fmt=info:ofi/fmt:kev:mtx:journal&genre=article&sid=ProQ:ProQ:abiglobal&atitle=Relationship+Between+Training+Of+Teachers+And+Effect Remler, D. K., & Ryzin, G. G. Van. (2015). Research Methods in Practice. Strategies for Description and Causation. https://www.ptonline.com/articles/how-to-get-better-mfi-results Rohita, Fitria, N., & Haryadi, D. (2018a). Pemanfaatan Aplikasi Penyusunan Perencanaan Pembelajaran (AP3) dalam Penyusunan Perencanaan Pembelajaran bagi Guru Taman Kanak-kanak di Jakarta. Jurnal Pengabdian Kepada Masyarakat, 24(2), 644–654. https://doi.org/10.24114/jpkm.v24i2.10168 Rohita, Haryadi, D., Fitria, N., & Bustan, R. (2019). Sistem informasi perangkat pembelajaran Untuk meningkatkan kualitas pendidik anak usia dini. Prosiding Seminar Nasional Pengabdian Masyarakat LPPM UMJ, September, 1–6. Rohita, R., Fitria, N., & Haryadi, D. (2018b). Pemanfaatan aplikasi penyusunan perencanaan pembelajaran (AP3) dalam penyusunan perencanaan pembelajaran bagi guru taman kanak-kanak di Jakarta. Jurnal Pengabdian Kepada Masyarakat, 24(2), 644. https://doi.org/10.24114/jpkm.v24i2.10168 Saifuddin, A. (2020). Penyusunan Skala Psikologi. Prenadamedia Group. Salsabil, Z., & Arfa, M. (2019). Efektifitas website Femaledaily.com dalam memenuhi kebutuhan informasi pengguna. Jurnal Ilmu Perpustakaan, 8(2), 199–210. Saparahayuningsih, S., Daryanti, M. E., & Badeni. (2020). Penyuluhan perencanaan pembelajaran kepada guru-guru Raudatul Atfal wilayah Kecamatan Seluma. Jurnal Pengabdian, 1(1), 16–26. Sari, H. E., & Prasetiawati, R. (2020). Analisis Sistem Informasi Customer Relationship Management Berbasis Web pada PT. INOVATIF TEKNIK MESINDO. Technomedia Journal, 5(1), 1–13. https://doi.org/10.33050/tmj.v5i1.881 Setyowati, E. O. T., & Respati, A. D. (2017). Persepsi Kemudahan Penggunaan, Persepsi Manfaat, Computer Self Efficacy, Dan Kepuasan Pengguna Sistem Informasi Akuntansi. Jurnal Riset Akuntansi Dan Keuangan, 13(1), 63. https://doi.org/10.21460/jrak.2017.131.281 Sijabat, S., Indah, T. A., Ramadhan, F., Ramadhani, A., & Hasibuan, S. H. (2021). Faktor-Faktor yang Menentukan Keberhasilan Produk Melalui Desain Logo pada Produk Og Home Care. KESATRIA: Jurnal Penerapan Sistem Informasi, 2(4), 195–199. https://doi.org/https://doi.org/10.30645/kesatria.v2i4.82 Sudjiman, P. E., & Sudjiman, L. S. (2018). Analisis Sistem Informasi Manajemen Berbasis Komputer dalam Proses Pengambilan Keputusan. TeIKa, 8(2), 55–66. https://doi.org/10.36342/teika.v8i2.2327 Sum, T. A., & Taran, E. G. M. (2020). Kompetensi pedagogik guru PAUD dalam perencanaan dan pelaksanaan pembelajaran. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 4(2), 543–550. https://doi.org/10.31004/obsesi.v4i2.287 Supriyatna, A., & Maria, V. (2017). Pengukuran Tingkat Kepuasan Pengguna Sistem Informasi DJP Online Pelaporan SPT Pajak. Prosiding SNATIF, 4, 147–154. Suratini, N. P. E., Sinarwati, N. K., & Atmadja, A. W. T. (2015). Pengaruh efektivitas sistem informasi akutansi dan penggunaan teknologi informasi akutansi terhadap kinerja individual pada PT. Bank Pembangunan Daerah Bali kantor cabang Singaraja. E-Journal S1 Ak Universitas Pendidikan Ganesha, 3(1). https://doi.org/http://dx.doi.org/10.23887/jimat.v3i1.4779 Suryana, D., & Rizka, N. (2019). Manajemen pendidikan anak usia dini berbasis akreditasi lembaga (Y. Rendy (ed.); Pertama). Prenadamedia Group. Susilo, S., Saibani, A., & Djati. (2016). Pedoman Penyelenggaraan PAUD. Bee Media Pustaka. Wahab, A., Syahid, A., & Junaedi, J. (2021). Penyajian Data Dalam Tabel Distribusi Frekuensi Dan Aplikasinya Pada Ilmu Pendidikan. Education and Learning Journal, 2(1), 40–48. https://doi.org/10.33096/eljour.v2i1.91 Wahyuni, M., Yuliantina, I., & Ritayanti, U. (2015). Penyusunan Rencana Pelaksanaan Pembelajaran PAUD (Issue 021). Direktorat Pembinaan Pendidikan Anak Usia Dini. Wahyuni, R., & Berliani, T. (2018). Pelaksanaan kompetensi pedagogik guru di sekolah dasar. Sekolah Dasar: Kajian Teori Dan Praktik Pendidikan, 27(2), 108–115. https://doi.org/https://doi.org/10.17977/um009v27i22018p108 Yakub. (2012). Pengantar sistem informasi. Graha Ilmu. Yusuf, A. M., Hasmizal, H., & Dini, N. (2021). Sistem Informasi Perhitungan Penyusutan Aktiva Tetap Menggunakan Metode Garis Lurus Berbasis Vb.Net Pada CV Ginanjar Sejahtera Mandiri Karawang. Jurnal Interkom: Jurnal Publikasi Ilmiah Bidang Teknologi Informasi Dan Komunikasi, 16(1), 38–45. https://doi.org/10.35969/interkom.v16i1.95